Akurasi kadar serum Secretory Leukocyte Protease Inhibitor (SLPI) dalam menunjang diagnosis kanker ovarium: suatu uji diagnostik - Putu Adi Sujana Putra; Ketut Suwiyoga; I Nyoman Gede Budiana; I Wayan Megadhana; I Nyoman Bayu Mahendra; I Made Darmayasa (DiscoverSys Inc., 2022)
Background: Ovarian cancer is one of the most common malignant tumors found in reproductive organs in vitro. Secretory Leukocyte Protease Inhibitor (SLPI) protein is essential for the growth of ovarian cancer cells, a protein that maintains the survival of ovarian cancer cells, inhibits antiproliferative effects, and reverses the proapoptotic effect of elastase. This study aims to evaluate the role of SLPI in diagnosing ovarium cancer. Methods: The research was conducted at the Obstetrics and Gynecology Polyclinic, Sanglah Hospital, Denpasar and the Prodia Laboratory. Sampling of this study has been carried out by previous researchers in research on the accuracy of serum levels of insulin-like growth factor binding protein 2 in diagnosing ovarian cancer. The research sample (intended sample) was women aged 18 years and over with ovarian tumors who came to the Obstetrics and Gynecology Polyclinic, Sanglah Hospital, Denpasar. Data were analyzed using SPSS versi 22 for Windows. Results: The proportion of epithelial types was significantly higher in the ovarian cancer group. In ovarian cancer samples, the most samples were obtained at FIGO III Stage. Median CA125 levels, RMI scores, and SLPI levels were significantly higher in the group with ovarian cancer. The cut off value of serum SLPI used in this study was 54,000 pg/ml which was obtained from preliminary analysis on 26 training samples. Sensitivity: 78.3; specificity:66.7%; Positive predictive value: 78.3%; Negative predictive value: 66.7% Accuracy: 73.6%. Conclusion: In a diagnostic test study to assess the accuracy of SLPI serum in supporting the diagnosis of ovarian cancer, it was found that SLPI serum had good sensitivity, specificity, PPV, NPV, and accuracy values. Latar Belakang: Kanker ovarium merupakan salah satu tumor ganas yang paling sering ditemukan pada organ reproduksi secara in vitro. Protein Secretory Leukocyte Protease Inhibitor (SLPI) sangat esensial untuk pertumbuhan sel kanker ovarium, protein yang menjaga kelangsungan hidup sel kanker ovarium, inhibisi efek antiproliferatif, dan membalikkan efek proapoptosis dari elastase. Penelitian ini bertujuan untuk mengevaluasi peran SLPI dalam mendiagnosis kanker ovarium. Metode: Penelitian dilakukan di Poliklinik Kebidanan dan Penyakit Kandungan RSUP Sanglah Denpasar dan Laboratorium Prodia. Pengambilan sampel penelitian ini sudah dilakukan oleh peneliti sebelumnya pada penelitian tentang akurasi kadar serum insulin-like growth factor binding protein 2 dalam mendiagnosis kanker ovarium. Sampel penelitian (intended sample) adalah wanita berusia 18 tahun ke atas dengan tumor ovarium yang datang ke Poliklinik Kebidanan dan Penyakit Kandungan RSUP Sanglah Denpasar. Hasil: Proporsi tipe epitelial secara signifikan lebih banyak pada kelompok kanker ovarium. Pada sampel kanker ovarium, didapatkan sampel paling banyak pada Stadium FIGO III. Median kadar CA125, skor RMI, dan kadar SLPI secara signifikan lebih tinggi pada kelompok dengan kanker ovarium. Nilai cut off serum SLPI yang digunakan pada penelitian ini adalah 54.000 pg/ml yang didapatkan dari analisa pendahuluan pada 26 training sample Sensitivitas:78,3; spesifisitas:66,7%; Nilai prediksi positif: 78,3%; Nilai prediksi negatif: 66,7% Akurasi: 73,6%. Kesimpulan: Pada penelitian uji diagnostik untuk menilai akurasi serum SLPI dalam menunjang diagnosis kanker ovarium didapatkan bahwa serum SLPI memiliki nilai sensitivitas, spesifisitas, PPV, NPV, dan akurasi yang baik.